The Effectiveness of Labor Law Protection for Workers Victims of Work Accidents: Between Normative Certainty and Implementation Problems - Nabila Annisa Hasibuan; Senny Kristina Putri; Sari Mahyuni Sitorus; Maulana Hafidz Pratama; Nurul Fattah Pohan (ISNU Sumatera Utara, 2024)
Protection of workers who have had work accidents is one of the important aspects in the implementation of fair industrial relations. Although Indonesia's labor law has provided various protection instruments through occupational safety and health regulations and employment social security, in practice there are still various problems such as low company compliance with occupational safety standards, non-fulfillment of the obligation to register workers in the social security program, and weak implementation of legal protection for workers who are victims of work accidents. This study aims to analyze the effectiveness of labor law protection for workers who have experienced work accidents and examine the relationship between the certainty of legal norms and the problems of their application in industrial relations practices. The research method used is normative legal research with a statutory approach and a conceptual approach through the study of laws and regulations, legal doctrines, and relevant literature. The results of the study show that normatively the labor law has provided a guarantee of protection through the obligation to implement occupational safety and health, the provision of the right to social security, and the responsibility of employers for workers who have a work accident. However, the effectiveness of these protections still faces obstacles in the implementation aspect, especially related to employer compliance, labor supervision, and the fulfillment of workers' rights. The conclusion of this study shows that labor law already has adequate protection instruments, but it is necessary to strengthen implementation and supervision so that legal protection for workers victims of work accidents can be realized in real terms.